Integrating sustainable development goals into teaching EFL - Cherednichenko, Galina; Nikitenko, Olga (My University, 2024)
Education for sustainable development (ESD) is UNESCO’s education sector response to the urgent and dramatic challenges the planet faces. To contain global warming before it reaches catastrophic levels means addressing environmental, social and economic issues in a holistic way. UNESCO’s ESD for 2030 education programme aims to bring about the personal and societal transformation that is necessary to change course. In the present study, the researchers aim to shed light to different ways to spread sustainable development into the curriculum, by specifically focusing on the ways to integrate environmental issues to EFL (English as a Foreign Language) lessons for university students.

Освіта для сталого розвитку (ОСР) — це відповідь сектору освіти ЮНЕСКО на нагальні та драматичні виклики, з якими стикається планета. Стримати глобальне потепління до того, як воно досягне катастрофічного рівня, означає комплексне вирішення екологічних, соціальних та економічних проблем. Освітня програма ЮНЕСКО ОУР до 2030 року має на меті здійснити особисту та суспільну трансформацію, необхідну для зміни курсу. У цьому дослідженні дослідники прагнуть пролити світло на різні шляхи поширення сталого розвитку в навчальній програмі, особливо зосередившись на способах інтеграції екологічних питань в заняття англійської мови як іноземної для студентів університетів.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; teaching English; викладання іноземної мови; англійська мова; екологічна освіта